Biopsychosocial Determinants of Multi Drug Resistant Tuberculosis in Surakarta - Lina Alfiyani; Setyo Sri Rahardjo; Bhisma Murti (Masters Program in Public Health, 2017)
Background: Tuberculosis is an infectious disease that poses serious threat to population health worldwide. Tuberculosis control enterprise becomes more complicated due to increasing number of Multi Drug Resistant Tuberkulosis (MDR-TB) cases. Globally there are approximately 580,000 cases of MDR-TB, with only 125,000 cases (20%) resolved. Indonesia ranks tenth in the world by the number of MDR-TB cases after Angola, Azerbaijan, Bangladesh, Belarus, Cina, Korea, Kongo, Etiopia, and India. This study aimed to analyzed the bio-psychosocial determinants of MDR-TB in Surakarta.Subjects and Method: This was an analytic observational study with case control design. The study was conducted in Dr. Moewardi Hospital and BBKPM, Surakarta, from September to November 2017. A sample consisting of 76 MDR-TB patients and 228 non MDR-TB patients were selected for this study by fixed disease sampling. The dependent variable was MDR-TB. The independent variables were age, drug-taking adherence, depression, comorbidity, drug side-effect, drug-taking supervisor, and family income. The data were collected using a set of questionnaire and analyzed by path analysis.Results: MDR-TB was affected by lack of drug-taking adherence (b= -1.7; 95% CI= -2.23 to -1.07; p=0.001) and comorbidity (b= 1.5; 95% CI= 0.76 to 2.30; p=0.001). Drug-taking adherence was affected by depression (b= -1.7; 95% CI= -2.60 to -0.79; p=0.001), drug side effect (b= -1.5; CI 95%= -2.10 to -0.86; p=0.001), and drug-taking supervisor (b=2.5; 95% CI= 1.84 to 3.06; p=0.001). Comorbidity was affected by age (b= 0.86; 95% CI= 0.12 to 1.61; p= 0.022).Conclusion: MDR-TB is directly affected by lack of drug-taking adherence and comorbidity. MDR-TB is indirectly affected by drug-taking supervisor, depression, and drug side effect.Keyword: bio-psychosocial determinants, MDR-TBCorrespondence: Lina Alfiyani. Masters Program in Public Health, Sebelas Maret University, Jl. Ir. Sutami 36 A, Surakarta, Central Java. Email: linabbt@gmail.com.Journal of Epidemiology and Public Health (2017), 2(3): 255-266https://doi.org/10.26911/jepublichealth.2017.02.03.07